The coverage of dengue and zika in selected Malaysian newspapers: an analysis of Berita Harian, Utusan Malaysia and The Star - Sedu, Nerawi; Mohamad Diah, Nurazzura (Centre for General Studies & Co-curricular Universiti Tun Hussein Onn Malaysia, 2017)
This study is aimed to analyze the coverage of news on dengue and zika in three mainstream daily Malaysian newspapers i.e. Berita Harian, Utusan Malaysia and The Star. The data for this study were collected from the print version of these newspapers for a period of a month i.e. November 2016. The newspapers were selected due to their circulation figures and they were also circulated nationwide. It is important to note that dengue and Zika are mosquito borne diseases or epidemics and they are spread by Aedes mosquito species. While dengue is regarded as health threats for decades in Malaysia, the first case of Zika infection was recorded quite recently, i.e. 31 August 2016. This study is significant in order to understand how the newspapers reported the news on dengue and Zika in helping the readers to be well informed on mosquito borne diseases and enhancing awareness of the diseases among Malaysians. The news or feature articles from the Berita Harian, Utusan Malaysia and The Star were analyzed using thematic analysis, focusing on the expressions or phrases and other news elements used by the newspapers to report the epidemics. The findings of the study showed that there were several common themes in the news or feature articles on dengue and Zika epidemics published by these newspapers.